Pengaruh Faktor Corporate Governance Terhadap Kualitas Audit Pada Perusahaan Sektor Keuangan Yang Terdaftar Di BEI - Arcelina Ikawati; Endang Masyitoh W.; Anita Wijayanti (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
This research aims to analyze the impact of corporate governance factors, such as ownership concentration, board size, and the presence of female directors, on audit quality. The research methodology involves secondary data analysis from the financial reports and audit reports of listed companies. The research findings indicate that ownership concentration and board size have a significant impact on audit quality, while the presence of female directors does not show a significant influence on audit quality. The results of this study are expected to provide a deep insight into the relationship between corporate governance practices and the level of audit quality provided by auditors. The practical implications of these findings can serve as a guide for practitioners, regulators, and other stakeholders in enhancing corporate governance and audit quality in the current business environment.